2011
DOI: 10.1589/jpts.23.33
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Floating Toe from the Viewpoint of the Structure of Foot Arch

Abstract: Abstract.[Purpose] The purpose of this research was to investigate the occurrence and mechanism of floating toe from the viewpoint of the structure of foot arch.[Subjects and Methods] The subjects were 65 adult females who had no history of orthopedic disease. Subjects stood on a pedoscope and we took images of the soles. According to a floatingtoe score which we created, we allocated subjects to a normal group and a floating-toe group using the obtained images. We measured the arch height percentage in the si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
43
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(44 citation statements)
references
References 7 publications
1
43
0
Order By: Relevance
“…Previous studies reported the association between floating toe and differences in arch height percentage (sitting vs. standing) in adult females3 ) and birth weight in infants4 ) . However, no study has investigated school age children.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported the association between floating toe and differences in arch height percentage (sitting vs. standing) in adult females3 ) and birth weight in infants4 ) . However, no study has investigated school age children.…”
Section: Introductionmentioning
confidence: 99%
“…Also, they do not seem to cause pain or need surgery. Untouched-toes are also called “floating-toes” [ 4 ]. In Japan, the number of children with untouched-toes is on the rise [ 2 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…With its complex anatomical structure, the foot plays a vital role in supporting body weight, absorbing shock, and moving the body forward when walking 1 , 2 , 3 ) . The toes also have the function of distributing load when walking 4 ) .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there have been occasional reports of “floating toe”, a condition that does not involve pain or deformity in which the toes do not make contact with the ground when standing 3 ) . In adults, the condition reportedly occurs as a result of surgery 9 , 10 ) .…”
Section: Introductionmentioning
confidence: 99%